Treatment of a patient with advanced esophageal cancer with a combination of mitomycin C and capecitabine: activation of the thymidine phosphorylase as active principle? - Hofheinz, Ralf-Dieter; Weißer, Andreas; Willer, Andreas; Hehlmann, Rüdiger; Hochhaus, Andreas (Onkologie, 2003)
Background: Both capecitabine, an oral prodrug of 5-fluorouracil (5-FU), and mitomycin C (MMC) have demonstrated activity as single agents in patients with gastrointestinal cancer. Furthermore, a combination of MMC with infusional 5-FU can induce tumor remission even in patients pretreated with 5-FU. Capecitabine and MMC act synergistically due to an upregulation of the thymidine phosphorylase activity by MMC in a human xenograft model. Patient: We sought to exploit these preclinically observed effects in a patient with esophageal cancer who was progressive after a first-line radiochemotherapy with 5-FU and cisplatin. He was treated with a combination of MMC and capecitabine on a compassionate use basis. A rapid remission lasting for about 6 months was observed. Conclusion: This is the first report on a combination therapy with capecitabine and MMC. The remission observed in our patient suggests that the preclinically observed synergy has clinical impact. This combination should be further investigated in prospective clinical trials.
Gesehen am 13.05.2022